2020
DOI: 10.3390/microorganisms8091385
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Rhizosphere and Non-Rhizosphere Microbial Community Structures and Functions of Camellia yuhsienensis Hu

Abstract: Camellia yuhsienensis Hu, endemic to China, is a predominant oilseed crop, due to its high yield and pathogen resistance. Past studies have focused on the aboveground parts of C. yuhsienensis, whereas the microbial community of the rhizosphere has not been reported yet. This study is the first time to explore the influence of seasonal variation on the microbial community in the rhizosphere of C. yuhsienensis using high-throughput sequencing. The results showed that the dominant bacteria in the rhizosphere of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…The seagrass habitats for their study was in the intertidal regions, while all the seagrasses in this study were collected from the coral reef ecosystem [ 16 ]. Moreover, previous studies have highlighted the importance of temperature in constructing the rhizosphere bacterial community anwhich exhibited seasonal variations [ 43 , 44 ]. Therefore, there may also be seasonal variations in the seagrass rhizosphere bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…The seagrass habitats for their study was in the intertidal regions, while all the seagrasses in this study were collected from the coral reef ecosystem [ 16 ]. Moreover, previous studies have highlighted the importance of temperature in constructing the rhizosphere bacterial community anwhich exhibited seasonal variations [ 43 , 44 ]. Therefore, there may also be seasonal variations in the seagrass rhizosphere bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…The soil physicochemical properties were measured according to Li et al (2020) . Soil temperature at 0–20 cm depth was measured using a Wdsen Electronic temperature recorder (iButton DS1925) during the entire experimental period ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient absorption from the soil and plant disease resistance is also affected by the soil microbiome, especially the rhizosphere microorganisms ( Bob et al, 1987 ; Jansson and Hofmockel, 2020 ). Although the rhizosphere microbial communities have been investigated in C. oleifera ( Zhang P. et al, 2020 ) and C. yuhsienensis ( Li et al, 2020 ), it remains difficult to compare differences in rhizosphere microbial community structures and functions due to inconsistent climate, soil conditions, and management practices. More importantly, none of the previous studies have reported on the microbial functions and their role in oil tea disease susceptibility and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Considering cultivated agricultural soils, Li et al (2019) observed that the relative abundance of Acidobacteria significantly increased in summer while Actinobacteria were significantly reduced in both spring and summer. However, research by Li et al (2020) found that Chloroflexi and Actinobacteria were significantly higher in summer while Acidobacteria were significantly higher in spring. Therefore, research needs to be conducted to clarify the effects of season on specific soil microorganisms in agricultural soils.…”
Section: Introductionmentioning
confidence: 92%